Type 2 diabetes mellitus aggravates coronary atherosclerosis in hypertensive individuals based on coronary CT angiography: a retrospective propensity score-based study - Jiang, Yu; Yang, Zhi-gang; Wang, Jin; Jiang, Li; Han, Pei-lun; Shi, Rui; Li, Yuan (Frontiers in Cardiovascular Medicine, 2024)
The effect of type 2 diabetes mellitus (T2DM) on coronary atherosclerosis detected on coronary computed tomography angiography (CCTA) in hypertensive patients has attracted increasing attention. This study investigated the relationships of T2DM with coronary artery plaque characteristics and semiquantitative CCTA scores in hypertensive patients.: In this single-center study, 1700 hypertensive patients, including 850 T2DM [HT(T2DM+)] and 850 non-T2DM [HT(T2DM-)] individuals, were retrospectively analyzed after propensity matching. Plaque type, extent, coronary stenosis, segment involvement score (SIS), segment stenosis score (SSS), and CT-based Leaman score (CT-LeSc) based on CCTA were assessed and compared between the two groups.Results: HT(T2DM+) patients had more coronary segments with calcified plaque (2.08±2.20 vs. 1.40±1.91), mixed plaque (2.90±2.87 vs. 2.50±2.66), nonobstructive stenosis (4.23±2.44 vs.3.62±2.42), and obstructive stenosis (1.22±2.18 vs. 0.78±1.51), a lower proportion of 1-vessel disease (15.3% vs. 25.5%), a higher proportion of 3-vessel disease (59.6% vs. 46.7%), and higher SIS (5.5±3.1 vs. 4.4±3.0), SSS (10.3±8.5 vs. 7.7±7.1), and CT-LeSc (9.4±5.6 vs. 7.9±5.2) than HT(T2DM-) patients (all P values <0.05). Multivariable analysis revealed that T2DM was an independent risk factor for calcified plaque [odds ratio (OR)=2.213], obstructive coronary artery disease (CAD) (OR=1.271), multivessel disease (OR=1.838), SIS>4 (OR=1.910), SSS>6 (OR=1.718), and CT-LeSc>5 (OR=1.584) in hypertension population (all P values <0.05).T2DM was independently associated with the presence of calcified coronary artery plaque and increased the risk of obstructive CAD, multivessel disease, and CT-LeSc >5 in 2 hypertensive patients. More attention should be given to the assessment and management for coronary atherosclerosis in hypertensive patients with T2DM, as this population may have a higher risk of cardiovascular events.